How can we begin to measure recovery? - Kenny Paul J; Krantz Barbara; Dodge Karen (BMC, 2010)
Abstract Background There is a lack of consensus in the addiction treatment literature regarding the definition of substance abuse "recovery". Methods This study utilized a review of the literature together with a participatory research design to construct a conceptual model of recovery from the perspectives of addiction treatment professionals, those recovering from addictions, and researchers. Results A multidimensional, comprehensive hypothetical model consisting of seven conceptual domains (physical, biomarker, psychological, psychiatric, chemical dependency, family/social, and spiritual) is presented. Each domain is operationally defined by identifying reliable and valid instruments that may be used to measure the domain. It is proposed that the conceptual model be tested using confirmatory factor analysis. Conclusions If empirically supported, this conceptual model would validate the hypothesized multidimensional nature of recovery and provide a potential means for assessing recovery in future treatment outcome studies.